Acute megakaryoblastic leukemia (excluding Down syndrome) remains an acute myeloid subgroup with inferior outcome in the French ELAM02 trial. (17th November 2017) - Teyssier, Anne-Charlotte; Lapillonne, Hélène; Pasquet, Marlene; Ballerini, Paola; Baruchel, André; Ducassou, Stephane; Fenneteau, Odile; Petit, Arnaud; Cuccuini, Wendy; Ragu, Christine; Preudhomme, Claude; Mercher, Thomas; et al.
ABSTRACT: We report the outcome of 27 children with de novo acute megakaryoblastic leukemia (AMKL) (excluding Down syndrome) enrolled in the French multicenter prospective study ELAM02 (2005-2011). There was no difference in gender, initial leukocyte count, CNS involvement, and complete remission rate (88.9%), as compared to other acute myeloid leukemia (AML) subtypes. AMKL patients had a significantly poorer outcome (5-year overall survival 54% [CI 95% 33%–71%] than children with other AML subtypes (5-year overall survival 73% [CI 95% 68%–77%] p = 0.02). Gender, age, CNS leukemia, hyperleukocytosis, complete remission or cytogenetic subgroups were not significant prognostic factors of disease-free survival. AMKL (excluding Down syndrom) remains an AML subgroup with inferior outcome.